“If the world is dystopic, why fear an apocalypse?” - Novák, Zsófia (Hungarian Journal of English and American Studies, 2021)
Book review:MacCormack, Patricia. The Ahuman Manifesto: Activism for the End of the Anthropocene. London: Bloomsbury Academic, 2020. 224 pages. ISBN 9781350081093. E-book. £15.83.